AN ANALYSIS OF THE TRANSLATION PRODUCTS FROM ENGLISH TEXT INTO INDONESIAN LANGUAGE - Jumiaty, Andi Asri (Fakultas Keguruan dan Ilmu Pendidikan, 2019)
This research found out the students’ error in translating English text into Indonesian language at Muhammadiyah University of Makassar. This research investigated students’ ways in translating and understanding the meaning of the text translated from English to Indonesian. A descriptive analysis was used in this research with the population was consisted of 107 students and applied purposive sampling technique and the chosen 60 students were taken as samples. The data was in the form of translation test. The result of the data analysis showed that the students’ error types in translating English text into Indonesian were 81.6 % generated translation was a literal translation and was 11 out of 60 students, or about 18.4% used the general translation from mistranslation or lexical meaning. And also it was found out that the students’ error in lexical meaning. And there were 43 % which has translated in general translation errors. This analysis was very useful for the teacher and students. It helped the students to know their weaknesses and difficulties in translating English text into Indonesian. It can be concluded that the students are directed to learn more and practice to translate about English text into Indonesian language